GeminiOne transcatheter edge-to-edge repair: comparative hemodynamic and biomechanical evaluation - Wang, Kai; Xu, Dongyang; Xiao, Bowen; He, Zhaoming; Tan, Jianfong; Kar, Saibal (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTranscatheter edge-to-edge repair (TEER) is frequently used to treat mitral regurgitation (MR) patients. Despite its widely reported efficacy, complications such as single-leaflet device attachment (SLDA) and loss of leaflet insertion (LLI) can lead to recurrent MR, which compromises the clinical outcomes.ObjectivesThis study compares the acute MR reduction and leaflet anchoring stability of a novel TEER device, GeminiOne (GEM), and MitraClip (MC).MethodsIn this study, ex vivo benchtop degenerative mitral regurgitation (DMR) and functional mitral regurgitation (FMR) models were used to evaluate the acute effectiveness of MR reduction by MitraClip XTW and GeminiOne 0626 in a BDC pulsatile flow duplicator. Furthermore, a benchtop study was performed to compare leaflet anchoring stability between XTW and GEM0626, in an attempt to investigate the likelihood of post-procedure leaflet detachment.ResultsThe results of the pulsatile flow evaluation from the DMR and FMR model demonstrate that both TEER devices effectively reduced the regurgitant fraction (DMR vs. GEM0626 vs. XTW, 59.21 ± 10.29% vs. 35.73 ± 6.62% vs. 43.50 ± 8.89%; FMR vs. GEM0626 vs. XTW, 56.99 ± 8.74% vs. 27.99 ± 11.30% vs. 28.13 ± 10.64%). However, in the leaflet stability study which compared the various TEER devices under full grasp and partial grasp conditions, the detachment force of the anchored leaflet for GeminiOne is significantly higher than that of MitraClip, especially for the partial grasp (full grasp detachment force: 7.89 ± 2.42 vs. 6.36 ± 0.96 N, p = 0.1214; partial grasp detachment force: 6.03 ± 2.05 vs. 2.97 ± 0.76 N, p = 0.0021).ConclusionIn the ex vivo pulsatile experiments, both GEM0626 and XTW are effective in terms of acute reduction of MR caused by DMR and FMR. However, in an anchored leaflet stability study, under partial grasp conditions, GEM0626 demonstrated a significantly higher leaflet detachment force. The better anchored stability of GeminiOne TEER may have long-term clinical benefits for MR treatment.